Estimation of the energy barrier for micelle-mediated nucleation growth on surfaces : strategic reduction and application in drug delivery - Vishwakarma, Mona (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Chemical Engineering and Technology